The Anatomy of the VAT - Keen, Michael (IMF Working Papers; Working Paper, 2013)
This paper sets out some tools for understanding the performance of the value added tax (VAT). Applying a decomposition of VAT revenues (as a share of GDP) to the universe of VATs over the last twenty years, it emerges that developments have been driven much less by changes in standard rates than by changes in 'C-efficiency' (an indicator of the departure of the VAT from a perfectly enforced tax levied at a uniform rate on all consumption). Decomposing C-efficiency into a 'policy gap' (in turn divided into effects of rate differentiation and exemption) and a 'compliance' gap (reflecting imperfect implementation), results pieced together for EU members suggest that the former are in almost all cases far larger than the latter, with rate differentiation and exemptions playing roles that differ quite widely across countries.